Methylacidimicrobium thermophilum AP8, a Novel Methane- and Hydrogen-Oxidizing Bacterium Isolated From Volcanic Soil on Pantelleria Island, Italy - Picone, Nunzia; Blom, Pieter; Wallenius, Anna J.; Hogendoorn, Carmen; Mesman, Rob; Cremers, Geert; Gagliano, Antonina L.; D’Alessandro, Walter; Quatrini, Paola; Jetten, Mike S. M.; Pol, Arjan; Op den Camp, Huub J. M. (Frontiers in Microbiology, 2021)
The Favara Grande is a geothermal area located on Pantelleria Island, Italy. The area is characterized high temperatures in the top layer of the soil (60 °C), low pH (3-5) and hydrothermal gas emissions mainly composed of CO2, CH4 and H2. These geothermal features may provide a suitable niche for the growth of chemolithotrophic thermoacidophiles, including the lanthanide-dependent methanotrophs of the phylum Verrucomicrobia. In this study, we started enrichment cultures inoculated with soil of the Favara Grande at 50 and 60 °C with CH4 as energy source and medium containing sufficient lanthanides at pH 3 and 5. From these cultures, a verrucomicrobial methanotroph could be isolated via serial dilution and floating filters techniques. The genome of strain AP8 was sequenced and based on phylogenetic analysis we propose to name this new species Methylacidimicrobium thermophilum AP8. The transcriptome data at µmax (0.051 ± 0.001 h-1, doubling time ~14 h) of the new strain showed a high expression of the pmoCAB2 operon encoding the membrane-bound methane monooxygenase and of the gene xoxF1, encoding the lanthanide-dependent methanol dehydrogenase. A second pmoCAB operon and xoxF2 gene were not expressed. The physiology of strain AP8 was further investigated and revealed an optimal growth in a pH range of 3 to 5 at 50 °C, representing the first thermophilic strain of the genus Methylacidimicrobium. Moreover, strain AP8 had a KS(app) for methane of 8 ± 1 µM. Beside methane, a type 1b [NiFe] hydrogenase enabled hydrogen oxidation at oxygen concentrations up to 1%. Taken together, our results expand the knowledge on the characteristics and adaptations of verrucomicrobial methanotrophs in hydrothermal environments and add a new thermophilic strain to the genus Methylacidimicrobium.